Estudo de custo-efectividade do aliscireno no tratamento da hipertensão em doentes com diabetes tipo 2 e nefropatia em Portugal - Gouveia, Miguel (2018)
Objectives: aliskiren is a direct human renin inhibitor that is efficacious in the treatment of high blood pressure in patients with diabetes mellitus type 2 and nephropathy. The purpose of this study is to provide an economic evaluation of aliskiren in a social perspective. We estimated the incremental cost-effectiveness of a therapeutical strategy based on aliskiren and losartan versus a strategy based on a losartan and placebo. The measures of effectiveness used were life expectancy, quality adjusted life years, and the incidence of end stage renal disease. Methods: the estimates of efficacy in clinical trials and other studies were extrapolated for a 20 years time horizon by using Markov chains with six month length cycles. We estimated the direct costs of the alternative strategies in the context of Portuguese clinical practice, including costs with aliskiren, losartan, other drugs, tests, doctor visits, and the costs of renal transplants. We also estimated indirect costs due to absenteeism and premature retirement from the labor market. Results: In the baseline case the strategy with aliskiren always dominates the placebo strategy, with mean costs inferior by €552,32 and superior effectiveness. The dominance result was robust to plausible variations in the time horizon, the management costs for patients with hypertension and type 2 diabetes and the transplant costs. The result was also robust to using different discount rates and to the non inclusion of indirect costs in the analysis. In a pessimistic alternative scenario with lower aliskiren efficacy in the initial cycle the incremental cost utility was €7246 per QALY ganied. Probabilistic sensitivity analysis shows that aliskiren is dominant witha 56,8% probability and that for willingnesses to pay between €20 000 and 30 000€ the probability aliskirenis cost-effective goes from 72,3% up to 76,6%. Conclusions: In the context of the Portuguese health system, the use of aliskiren is cost-effective. Thus aliskiren is a valuable addition to the therapeutic arsenal for the treatment of patients with diabetes mellitus type 2, high blood pressure and nephropathy.